Respostas

2014-08-21T01:57:51-03:00
f(x)=2x

a)
f(x+h)-f(x)

f(x+h) = vc substitui x na função "2(x)" por x+h 
vai ficar
f(x+h)=2(x+h)

f(x+h)-f(x)\\\\2(x+h)-(2x)\\\\2x+2h-2x\\\\(2x-2x)+2h\\\\0+2h\\\\2h\\\\RESPOSTA:\\\\\boxed{f(x+h)=f(x)=2h}
::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::
b)
 \frac{f(x+h)-f(x)}{h}

como vimos f(x+h)-f(x) = 2h.....então nao vou fazer esse calculo de novo
vai ficar
 \frac{2h}{h} =2\\\\\\RESPOSTA\\\\ \frac{f(x+h)-f(x)}{h}=2